أثر استراتيجية الانشطة المتدرجة في تحصيل طالبات الصف الثاني المتوسط في مادة الجغرافية Effect Of The Strategy Of Gradient Activities In The Scores Of Female Students Of 2nd Intermediate Grade In Geography Material - Jinan M. Hamza جنان مرزة حمزة (Journal Of Babylon Center For Humanities Studies, 2019)
This research aims to identify the impact of the strategy of gradual activitiesIn the achievement of second-grade students in geography, To investigate the research objective, the researcher formulated the following zero hypothesis: There is no difference with statistical significanceAt the level of significance (0.05)Between the average achievement of students in the experimental group Who study the Arab world geography Using a gradual activity strategy And the average score of students of the control group Who study the Arab world geography in the usual way. The researcher chose a trial design with partial control Of the control and experimental groups With a post-test, She chose randomly Marrowj school for girls In the center of Babil province Affiliated to the General Directorate of the Education of Babylon, In the same manner, Division (e)had been selected, To represent the experimental group which has (33) students, and the division (b) To represent the control group which has (31) students Which studied the geography of the Arab world The researcher conducted an equivalence between the students of the two groups of the research in the following variables: the age of the students calculated by the months, Parents' education achievement and IQ test. a-The researcher identified the study material to be studied during the trial period And formulated behavioral goals amounted to (110) Behavioral goals And after presenting them to a group of arbitrators In the teaching methods of social, psychological and geographical sciences that been Modified The researcher prepared educational plans Of the subjects and geographical topics have been modifiedDuring the duration of the experiment The researcher taught the two research groups. b-During the duration of the experiment that lasted a full semester and after the end of the experiment. c-The researcher applied the achievement test and the measure of direction on the two groups of research. The researcher used The following statistical means (T.test for two independent samples and (k2) and code (20) Pearson correlation coefficient and coefficient of difficulty Equivalent Discriminatory power and equivalent the Effectiveness of alternatives And Spearman Brown equation. By the result the researcher achieved, she reached several conclusions: 1.The strategy has helped to generate new ideas and meanings for students through their ability to analyze, interpret and criticize and rely on themselves in the research and investigateof facts and information. 2.The use of the strategy contributes to the process of teaching geography in a sequential, interdependent and integrated manner. يهدف هذا البحث الى التعرف على اثر استراتيجية الانشطة المتدرجة في تحصيل طالبات الصف الثاني متوسط في مادة الجغرافية وللتحقق من هدف البحث صاغت الباحثة الفرضية الصفرية الاتية : لا يوجد فرق ذو دلالة احصائية عند مستوى دلاله (0,05) بين متوسط درجات تحصيل طالبات المجموعة التجريبية اللائي يدرسنّ مادة جغرافية الوطن العربي باستعمال استراتيجية الانشطة المتدرجة ومتوسط درجات تحصيل طالبات المجموعة الضابطة اللاتي يدرسنّ مادة جغرافية الوطن العربي بالطريقة الاعتيادية ,واختارت الباحثة تصميماً تجريبياً ذو ضبط جزئي للمجموعتين الضابطة والتجريبية ذات الاختبار البعدي واختارت بالطريقة العشوائية متوسطة المروج للبنات في مركز محافظة بابل التابعة الى المديرية العامة لتربية بابل وبطريقة نفسها تم اختيار شعبة (هـ) لتمثل المجموعة التجريبية والبالغ عدد طالباتها (33) طالبه وشعبة (ب) لتمثل المجموعة الضابطة والبالغ عدد طالباتها (31) طالبه التي درست جغرافية الوطن العربي واجرت الباحثة تكافؤاً بين طالبات مجموعتي البحث في المتغيرات الاتية : العمر الزمني للطالبات محسوبة بالشهور التحصيل الدراسي للوالدين واختبار الذكاء أ‌-فقد حددت الباحثة المادة الدراسية التي ستدرس اثناء مدة التجربة وصاغت لها أهدافاً سلوكية بلغت (110) هدفاً سلوكياً وبعد عرضها على مجموعة من المحكمين في طرائق تدريس الاجتماعيات والعلوم التربوية والنفسية والجغرافية تم التعديل عليها واعدت الباحثة خططاً تدريسية للموضوعات المقرر والجغرافية تم التعديل عليها واعدت الباحثة خططاً تدريسية للموضوعات المقرر تدريسها في اثناء مدة التجربة وقد درست الباحثة مجموعتي البحث ب‌-خلال مدة التجربة التي استمرت فصل دراسي كامل وبعد انتهاء التجربة ت‌-طبقت الباحثة اختبار التحصيل على طالبات مجموعتي البحث. استعملت الباحثة الوسائل الاحصائية الاتية ( الاختبار التائي لعينتين مستقلتين (t-test)ومربع كأي (كا2) وكود(20) ومعامل الارتباط بيرسون ومعامل الصعوبة ومعادلة القوة التميزية ومعادلة فاعلية البدائل المخطوئة ومعادلة (سبيرمان وبراون) وتوصلت الباحثة على تفوق المجموعة التجريبية اللاتي درسن مادة جغرافية الوطن العربي باستعمال استراتيجية الانشطة المتدرجة على طالبات المجموعة الضابطة اللاتي درسن المادة نفسها بالطريقة الاعتيادية. وفي ضوء النتائج التي توصلت اليها الباحثة توصلت الى عدة استنتاجات منها 1-ساعدت الاستراتيجية على توليد افكار ومعان جديدة لدى الطالبات من خلال قدرتهن على التحليل والتفسير والنقد والاعتماد على انفسهن في البحث والتقصي عن الحقائق والمعلومات 2-يسهم استعمال الاستراتيجية في عملية تدريس الجغرافية بطريقة متسلسلة ومترابطة ومتكاملة.